2014
DOI: 10.1590/1982-0194201400004
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of the Echinodorus macrophyllus in induced renal injury

Abstract: Objective: Evaluating the renoprotective effect of Echinodorus macrophyllus in acute kidney injury induced by cyclophosphamide in rats. Methods: Experimental research with Wistar rats, male adults, distributed into groups, namely: Controladministration of 1.5 ml sodium chloride 0.9% intraperitoneally; Echinodorous -administration of 2g/kg of Echinodorus macrophyllus by gavage for five days; Cyclophosphamide -administration of cyclophosphamide 150mg/kg intraperitoneally; and Cyclosphosphamide + Echinodorus -adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Traditionally, the Amazonian population uses extracts from the leaves of E. macrophyllus, from infusion, decoction, or maceration methods, in water or alcohol, to treat urinary system disorders, as they are known to be powerful diuretic agents. In view of popular usage, Nascimento et al [171] demonstrated that preconditioning with E. macrophyllus attenuated cyclophosphamide-induced acute kidney injury in rats as evidenced by increased creatinine clearance and reduced oxidative metabolites in urine and increased reserve of antioxidant enzymes in renal tissue.…”
Section: Echinodorus Macrophyllus (Kunth) Michelimentioning
confidence: 99%
“…Traditionally, the Amazonian population uses extracts from the leaves of E. macrophyllus, from infusion, decoction, or maceration methods, in water or alcohol, to treat urinary system disorders, as they are known to be powerful diuretic agents. In view of popular usage, Nascimento et al [171] demonstrated that preconditioning with E. macrophyllus attenuated cyclophosphamide-induced acute kidney injury in rats as evidenced by increased creatinine clearance and reduced oxidative metabolites in urine and increased reserve of antioxidant enzymes in renal tissue.…”
Section: Echinodorus Macrophyllus (Kunth) Michelimentioning
confidence: 99%